DERBENT AS A MONUMENT OF THE GLOBAL HISTORY AND CULTURE - Gadziev, M S (History, Archeology and Ethnography of the Caucasus, 2015)
The article is devoted to the short review of medieval history of Derbent, its archaeological, architectural and epigraphic monuments.